Development And Validation Of A Musical Creativity Module For Lower Primary School Children In Malaysia - Jamaludin, Juriani (2019)
Enshrined in the Malaysian Education Blueprint 2013-2025 is the Ministry’s Educatian goal of producing balanced and harmonious individuals who will contribute to the country’s creative and innovative human capital. To achieve this, values that develop creativity and innovation must be instilled in all children through both teaching and learning at an early stage of the education system. This study hopes to be a part of this effort by developing, implementing and testing the efficacy of a musical creativity module for eight -year old primary school children. The module which hopes to enhance children’s creative thinking skills in music has been designed based on the divergent thinking criteria in Webster’s Theory of Creativity (Musical Extensiveness, Musical Flexibility and Musical Originality and Musical Syntax). The research discusses the content and structure of this Musical Creativity Module along the lines of the ADDIE Model of Instructional Design. Three important development phases were identified using the Delphi Technique: Needs Analysis, Design and Development and Validation of the Module.